The case for a positive euro area inflation target: Evidence from France, Germany and Italy - Klaus Adam; Erwan Gautier; Sergio Santoro; Henning Weber (European Central Bank (ECB), 2021)
Using micro price data underlying the Harmonized Index of Consumer Prices in France, Germany and Italy, we estimate relative price trends over the product life cycle and show that minimizing price and mark-up distortions in the presence of these trends requires targeting a significantly positive in ation target. Relative price trends shift the optimal in ation target up from a level of zero percent, as suggested by the standard sticky price literature, to a range of 1.1%- 2.1% in France, 1.2%-2.0% in Germany, 0.8%-1.0% in Italy, and 1.1-1.7% in the Euro Area (three country average). Differences across countries emerge due to systematic differences in the strength of relative price trends. Other considerations not taken into account in the present paper may push up the optimal in ation targets further. The welfare costs associated with targeting zero in ation turn out to be substantial and range between 2.1% and 4.5% of consumption in present-value terms.
Keywords: E31; E52; 330; Optimal ination target; micro price trends; welfare